2012
DOI: 10.1213/ane.0b013e31824d6168
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Ilioinguinal/Iliohypogastric Nerve Blocks for Persistent Inguinal Postherniorrhaphy Pain

Abstract: Ultrasound-guided lidocaine blocks of the ilioinguinal and iliohypogastric nerves, at the level of the anterior superior iliac spine, are not useful in diagnosis and management of persistent inguinal postherniorrhaphy pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 26 publications
0
57
1
3
Order By: Relevance
“…The importance of using placebo can be seen in a well-designed randomized, placebo-controlled, double-blinded crossover trial examining the effects of peripheral nerve blockade in postherniotomy pain patients. 28 The results showed the same pain response after placebo compared with after local anesthetic blockade and also found a high proportion (5 of 12) of patients were placebo responders, casting doubt on much of the previous research on peripheral nerve blockade.…”
Section: Discussionmentioning
confidence: 74%
“…The importance of using placebo can be seen in a well-designed randomized, placebo-controlled, double-blinded crossover trial examining the effects of peripheral nerve blockade in postherniotomy pain patients. 28 The results showed the same pain response after placebo compared with after local anesthetic blockade and also found a high proportion (5 of 12) of patients were placebo responders, casting doubt on much of the previous research on peripheral nerve blockade.…”
Section: Discussionmentioning
confidence: 74%
“…A double blinded, randomized, crossover trial showed no efficacy when compared with placebo [70]. The authors hypothesized that the GF nerve may have a greater role in lower abdominal and pelvic pain than realized [70].…”
Section: Iliohypogastric Nervesmentioning
confidence: 99%
“…QST has been used to document the somatosensory profiles of such deficits and to quantify the effects of treatments on different forms of pain, such as allodynia and hyperalgesia [32]. Investigators have tried to establish the analgesic and sensory effects of ultrasoundguided nerve blocks in specific postprocedural pain syndromes [33], but no recommendations for therapeutic changes could be made on the basis of the data obtained.…”
Section: • • Therapeutic Interventions and Prediction Of Therapeutic Oumentioning
confidence: 99%